Openness, Growth, and Productivity in Indonesia's Development Agenda - Varela, Gonzalo J. (World Bank, Jakarta, 2015)
The government of Indonesia has set ambitious goals for development, envisioning high, inclusive and sustainable growth over the coming years. Indonesia has the resource endowments and the potential to attain these goals. To turn this potential into reality, the private sector needs to increase investment and productivity to become a growth-engine for quality jobs to meet the needs of a rapidly increasing labor force. This note argues that maintaining and deepening Indonesia s integration into the global marketplace will facilitate this process. Policies that encourage greater integration into the world economy are no substitute, however, for a broader development strategy that takes into account, on one hand, that public support may be needed to improve the general business climate and quality of human capital, particularly logistics services, and on the other, that there remains room for corrective action to compensate groups that may be negatively impacted in the process of integration into the world economy.